Alginate-based hydrogel fiber as a restricted access material for microextraction of drugs in biological samples. (15th October 2022) - Guzella, Camille S.; Souto, Dênio E.P.; Silva, Bruno J.G.
Abstract: A novel lab-made alginate-based hydrogel device was successfully prepared and applied as a sorption material for the solid-phase microextraction of drugs (fluoxetine and its metabolite, norfluoxetine) in human plasma, with subsequent determination by high performance liquid chromatography–fluorescence detection (HPLC-FD). When supported in a polypropylene hollow fiber, the alginate was able to extract the analytes and functioned as a restricted access material, excluding >95 % of proteins from the biological matrix. The results indicate the potential use of this phase/device for quantitative drugs extraction from biological matrices at concentrations compatible with those typical in the literature (0.5 μg mL −1 ), and with satisfactory precision (13.4 % for fluoxetine and 6.2 % for norfluoxetine). Such outcomes, promoted by a simple and inexpensive material, open a new perspective of exploration of hydrogels as the sorption phase in biological matrices, a concept previously unexplored in the literature. Graphical abstract: Unlabelled Image Highlights: Application of alginate-based hydrogel fibers as sorption material. Alginate hydrogel acts as a restricted access material for plasma protein exclusion. Allows direct extraction of drugs from human plasma without needing additional steps such as protein precipitation. Inexpensive, simple, and efficient sorption phase for drug extraction from biological matrices.